ASSISTÊNCIA DE ENFERMAGEM AO PACIENTE COM HIPOGLICEMIA E SUA RELAÇÃO COM A INSULINOTERAPIA - Melo de Sousa, Fábio; de Souza Pereira, Vagner; Viana Borges, Franz; Rigueti Brasil, Thaís (LINKSCIENCEPLACE, 2026)
Diabetes mellitus (DM) is characterized by the change in the functioning of the body, causing a high concentration of blood sugar. The problem can have several causes, and outcome of the body’s inability to produce or properly use insulin, a substance produced by the pancreas to control precisely the levels of blood sugar. The therapy requires effective participation of the patient in order to take care of themselves for their own benefit, to maintain life, health and well-being, since the schedule requires the coordination of medications, diet and exercise on a daily routine of order to maintain blood glucose near normal levels. Therefore, this study aimed to analyze the nursing care of patients with hypoglycemia and their relationship to insulin. The methodology was developed through qualitative research, which aimed to examine the nursing care of diabetic patients treated with insulin and its relationship to hypoglycemia. To this end, interviews were conducted through semi-structured questionnaire with 45 diabetic patients seen in family health program in Bom Jesus do Norte -ES, in the months of August and September 2014. It is concluded that it is necessary greater empowerment of the nursing staff so that it can act together with diabetes patients, guiding them in their doubts, making them aware of the importance of being active agents in the management of the disease, which leads to better outcomes in the treatment and consequently in their quality of life.